Increasing trend of HIV/AIDS among Arab and Jewish male persons in Israel, 1986–2010. Issue 5 (22nd November 2012) - Mor, Z; Grayeb, E; Beany, A; Grotto, I
Abstract : Objectives: The aim of the study was to compare the HIV/AIDS burdens in Jewish and Arab Israeli males, as HIV/AIDS affects different population groups disproportionally. Methods: The National HIV/AIDS Registry (NHAR) was used as the source of HIV/AIDS infection records, while the Israeli Central Bureau of Statistics was used to determine group‐specific disease rates. Results: Between 1986 and 2010, 3499 HIV/AIDS‐infected male Israelis were reported to the NHAR: 3369 (96.3%) Jews and 130 (3.7%) Arabs, with an average annual incidence of 5.5 and 0.8 per 100 000 of the population, respectively ( P = 0.05). Of the Jews, 1018 (29.9%) were born in Ethiopia, while 2389 were Jews who were not Ethiopian‐born (JNE). Most of the Arabs ( n = 99; 74.8%) were Muslims, followed by Christians (21; 16.2%) and Druze (13; 10%). AIDS rather than HIV infection at the time of reporting was diagnosed in 568 (23.8%) of the JNE and 31 (23.8%) of the Arabs (p = 1). The most affected age group was those aged 25–34 years among the JNE and those aged 20–24 years among the Arabs, and the respective cumulative death rates were 24.9% ( n = 594) and 32.5% ( n = 40) ( P = 0.1). The point prevalences in 2010 were 58.4 and 11.4 per 100 000 for JNE and Arabs, and in adults aged 15–59 years they were 71.5 and 26.3 per 100 000, respectively. In Muslims, Christians and Druze, the point prevalences were 4.2, 11.2 and 7.1 per 100 000, and in adults aged 15–59 years they were 22.6, 42.9 and 29.4, respectively. The most common risk group among JNE was men who have sex with men (MSM; n = 1223; 51.2%), followed by injecting drug users ( n = 661; 27.7%), while among Arabs it was MSM ( n = 63; 48.1%), followed by heterosexuals ( n = 36; 27.3%). Conclusions: The HIV/AIDS burden in Israeli Arab males was significantly lower than that in Jews, and in both populations the most common risk group was MSM, with the proportion of MSM increasing with time.